Effect of concentration of starch in the properties morphological and structural of porous ceramic based on expansive clays (2020)
In this article is used the sacrificial material method to generate different porosities between 44.42% and 69.14% in ceramics based on expansive clays from San Jose de Cúcuta metropolitan area, Colombia, to analyze the effect of concentration of starch (porogenic agent) in the morphological and structural properties using calcium carbonate as a stabilizer. The porous ceramics was characterized by X-ray diffraction, scanning electron microscopy and energy dispersive X-ray spectroscopy. Finally, the images were analyzed with the software Image J, Image Tool and Origin. The results showed that the weight concentration of starch has a relationship with the average pore size, the number of pores and the porous area of the samples where the percentage of porous area and the average pore size of the mixtures increases as starch is added due to the decay of the sacrificial material. The number of pores of the mixtures decreased by increasing the weight concentration of the starch due to the agglomeration of the starch.